The effect of pruning Acropora palmata as a strategy for obtaining living tissue for reef restoration actions - Padilla Souza, Claudia (2023)
Introduction: Coral reefs are highly degraded ecosystems, for which it has been necessary to implement active restoration actions to recover their structure and functioning. Asexual propagation has been implemented to obtain small fragments (~10 cm) from the distal branches of donor colonies of corals of the species Acropora palmata, to subsequently relocate them in the reef substrate, simulating the dispersion effect that occurs naturally in the species, which in this work is called assisted propagation. However, it is necessary to evaluate the effects of this technique, such as the number of fragments that can be obtained from each colony, the tissue recovery period of the donor colonies and fragments.  Objective: To address the effect of pruning on donor colonies by estimating the percentage of live tissue removed from donor colonies of A. palmata and their recovery rate after 30-months.  Methods: Four surveys were carried out: before, immediately after pruning, one month after outplanting, and 30 months after pruning on four colonies of A. palmata located in the Parque Nacional Costa Occidental de Isla Mujeres, Punta Cancún and Punta Nizuc in the Mexican Caribbean. Photogrammetry-based 3D modeling was performed using Agisoft Metashape Pro software, while tissue surface area, radial and apical growth were obtained using CloudCompare software.  Results: After fragment collection, the material used in the assisted propagation represents less than 12% of the living tissue. After one month, the donor colonies showed a recovery of 5%, with new tissue covering the cut areas. The donor colonies lost on average 65 % of living tissue after four hurricanes, and in one case the colony was lost all together, but with the outplanted fragments the genotype could be preserved.  Conclusions: Assisted propagation could increase living tissue of branching corals in relatively short intervals of time, without serious damage to the donor colony if less than 12 % is removed.